10 KETRAMPILAN ABAD 21 TERATAS YANG DAPAT DIKEMBANGKAN MELALUI PENERAPAN METODE PROBLEM BASED LEARNING - Santosa, Wahyuningsih; Nilawati, Yuana Jatu; Murtanto, Murtanto; Kasuma Ali, Jati (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2025)
This study aims to analyze the role of the Problem Based Learning (PBL) learning method in facilitating the development of skills that are very much needed in today's era. The study was conducted quantitatively descriptively by distributing questionnaires to 151 students and alumni of the Faculty of Economics and Business, Universitas Trisakti who carried out the learning process with the PBL method. The data collected were processed using SPSS. The results of the study indicate that PBL is an active learning method that is able to facilitate the development of student skills that are very much needed to achieve success in the 21st century. The results of the ranking of skills developed through PBL show the top 10 skills, namely cooperation skills, communication skills, negotiation and conflict management skills, analytical skills, results-oriented skills, leadership skills, decision-making skills, innovation/creativity skills, critical thinking skills, and maturity skills. With these results, it can be recommended to expand the implementation of PBL in other study programs and to provide adequate training for lecturers.